India-Pakistan relations after Constitutional Change: Retraction of Article 370 and 35-A - Amar Jahangir; Dr. Anbrin Khawaja; Tahir Abdul Khaliq, (Dialogue Social Science Review (DSSR), 2025)
Since the beginning of time, India and Pakistan have been at odds over the Jammu and Kashmir Conflict. Along with the Kargil war in 1999 over Kashmir, both nuclear powers fought three wars in the 1948, 1965, and 1971. Article 370 and 35-A of the Indian Constitution are directly related to the special status of the state Jammu and Kashmir. India violated the Shimla Agreement and UN Security Council resolutions on August 5, 2019, when it overthrew these articles and annexed its seized region of Jammu and Kashmir. This unilateral move increased friction between India and Pakistan and caused substantial social, political, and economic turmoil. Analytical and descriptive methods are employed to examine the political, social, cultural, and bilateral effects of constitutional change by using secondary data in this qualitative research paper. The main objective of this paper is discussing the relationship between India and Pakistan following the repeal of Articles 370 and 35A. Keywords: Pakistan, India, Jammu and Kashmir, Constitutional Change and Retraction of Article 370 & 35-A